2010
DOI: 10.1021/cm102463t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Scale and Nanoscale Morphology of P3HT:PCBM Bulk Heterojunctions: Energy-Filtered TEM and Low-Dose HREM

Abstract: The performance of bulk heterojunction organic photovoltaic devices is critically dependent on the morphology of the active layer. Here we describe the combination of two electron microscopy techniques to quantitatively examine the molecular level structure and mesoscopic domain morphology of the active layer of poly(3-hexylthiophene):[6,6]-phenyl-C61-butyric acid methyl ester P3HT:PCBM bulk heterojunction solar cells. Energy-filtered transmission electron microscopy (EFTEM) revealed the nanoscopic, interpenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 36 publications
13
136
0
Order By: Relevance
“…The 22±4 eV image utilized the plasmon peak of the p-type organic semiconductor to enhance the contrast in the electron energy loss spectra, and the thickness map is obtained from the ratio of unfiltered and filtered image, yielding pixel by pixel values of t/l, where t is film thickness in nanometre and l is the electron mean free pathway. Both the 22 ± 4 eV image and the thickness map suggest that there is indeed an additional layer underneath C8-BTBT 39,40 . Further indication of vertical phase separation in the C8-BTBT:PS film was observed by scanning electron microscopy using a thicker film with a higher percentage of PS, showing a similar phase-separated structure, where the PS layer was sandwiched between the C8-BTBT and PVP film (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The 22±4 eV image utilized the plasmon peak of the p-type organic semiconductor to enhance the contrast in the electron energy loss spectra, and the thickness map is obtained from the ratio of unfiltered and filtered image, yielding pixel by pixel values of t/l, where t is film thickness in nanometre and l is the electron mean free pathway. Both the 22 ± 4 eV image and the thickness map suggest that there is indeed an additional layer underneath C8-BTBT 39,40 . Further indication of vertical phase separation in the C8-BTBT:PS film was observed by scanning electron microscopy using a thicker film with a higher percentage of PS, showing a similar phase-separated structure, where the PS layer was sandwiched between the C8-BTBT and PVP film (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…3b. Note that the energy window is centred at 19 ± 4 eV to provide maximum contrast for P3HT, and as a result, the bright regions in the micrographs correspond to P3HT-rich domains 33 . It was observed that the P3HT and SD-P3HT domains overlap with each other over the whole film, indicating the formation of an interpenetrating network with no visible isolated P3HT fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…Similar structures have been observed previously with TEM in P3HT domains inside P3HT:PCBM blends. [ 40 ] …”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%